Aspectos ultrassonográficos da glândula tireoide hígida em equinos - Viana, Gustavo Fernandes [UNESP] (2015)
The application of ultrasonography can provide valuable data for efficient clinical and surgical intervention in cases of thyroid disorders. However, there are few studies related to the use of the USG as an evaluation method of the thyroid gland (TG) in horses. The objective was to establish analysis parameters of healthy TG in adult horses by B and Doppler mode ultrasonography. Eleven horses (twenty-two thyroid lobes) were selected through negative for thyroid disorders on clinical examination, laboratory (free thyroxine by equilibrium dialysis), USG and cytology. It was determined the means and standard deviations of dimensions of the thyroid lobes (TLs), and peak systolic velocity, resistive and pulsatility index their respective cranial thyroid arteries (ACTs). The contours, echotexture, echogenicity and parenchymal color flow pattern (PCFP) thyroid were also evaluated. There were no significant differences between values obtained for the left and right TLs. The same happened to left and right ACTs. The USG proved an efficient diagnostic methodology for defining the TG reference values in adult horses. Although the left and right TLs may present distinct general format in the same animal, other parameters as the dimensions, contours, parenchymal and vascular characteristics were similar. From these criteria, if one of the lobes is affected by thyroid disorders, the contralateral lobe could form the basis for evaluation of another lobe changed. In addition, the study unilateral ACT spectral Doppler parameters may be used to evaluate diffuse thyroid disorder